KARAKTERISTIK TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI BERBASIS AGROEKOSISTEM LAHAN SAWAH IRIGASI DI PROVINSI BALI - Suharyanto Suharyanto (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
Household food security level essentially is the ability of households meet food sufficiency. These capabilities are greatly influenced by many complex factors, but  generally  associated  with  changes  in  behavioral  aspects  of  food  production, consumption and allocation of households resources. The purpose of this study was to analyze  the  level  of  household  food  security  based  on  low  land  rice  irrigated.  The study was conducted in three districts of rice production center in the province of Bali in 2012, i.e. Tabanan district, Gianyar and Buleleng. Data collection was conducted through interviews with 216 respondents. Household food security was measured by cross classification of the share of food expenditure and consumption of energy. The results  of  the  analysis  showed  58.33  %  of  households  have  a  lower  share  of  food expenditure  and  41.67%  household  have  higher  share  of  food  expenditure.  In aggregate  86.57%  of  farm  households  is  quite  in  consuming  energy  and  13.43% is less  in  energy  consume.  The  level  of  household  food  security  of  farmers  in  the aggregate 49.07% of the household were categorized as secure, 37.9% as vulnerable, 8.79% as insufficient, and 4.17% as insecure. There is a correlation between the level of  household food  security  with  age  of  housewife,  level  of  education,  farm  size  and household income.